Examining the impact of a social skills training program on preschoolers’ social behaviors: a cluster-randomized controlled trial in child care centers - Marie-Pier Larose; Isabelle Ouellet-Morin; Francis Vergunst; Frank Vitaro; Alain Girard; Richard E. Tremblay; Mara Brendgen; Sylvana M. Côté (BMC Psychology, 2020)
Abstract Background Preschoolers regularly display disruptive behaviors in child care settings because they have not yet developed the social skills necessary to interact prosocially with others. Disruptive behaviors interfere with daily routines and can lead to conflict with peers and educators. We investigated the impact of a social skills training program led by childcare educators on children’s social behaviors and tested whether the impact varied according to the child’s sex and family socio-economic status. Methods Nineteen public Child Care Centers (CCC, n = 361 children) located in low socio-economic neighborhoods of Montreal, Canada, were randomized into one of two conditions: 1) intervention (n = 10 CCC; 185 children) or 2) wait list control (n = 9 CCC; 176 children). Educators rated children’s behaviors (i.e., disruptive and prosocial behaviors) before and after the intervention. Hierarchical linear mixed models were used to account for the nested structure of the data. Results At pre-intervention, no differences in disruptive and prosocial behaviors were observed between the experimental conditions. At post-intervention, we found a significant sex by intervention interaction (β intervention by sex = − 1.19, p = 0.04) indicating that girls in the intervention condition exhibited lower levels of disruptive behaviors compared to girls in the control condition (f2 effect size = − 0.15). There was no effect of the intervention for boys. Conclusions Girls may benefit more than boys from social skills training offered in the child care context. Studies with larger sample sizes and greater intervention intensity are needed to confirm the results. Trial registration Current clinical trial number is ISRCTN84339956 (Retrospectively registered in March 2017). No amendment to initial protocol.